Impaired perception of temporal fine structure and musical timbre in cochlear implant users - Heng, Joseph (2011)
Cochlear implant (CI) users demonstrate severe limitations in perceiving musical timbre, a psychoacoustic feature of sound responsible for ‘tone color’ and one’s ability to identify a musical instrument. The reasons for this limitation remain poorly understood. In this study, we sought to examine the relative contributions of temporal envelope and fine structure for timbre judgments, in light of the fact that speech processing strategies employed by CI systems typically employ envelope extraction algorithms. We synthesized “instrumental chimeras” that systematically combined variable amounts of envelope and fine structure in 25% increments from two different source instruments with either sustained or percussive envelopes. CI users and normal hearing (NH) subjects were presented with 150 chimeras and asked to determine which instrument the chimera more closely resembled in a single-interval two-alternative forced choice task. By combining instruments with similar and dissimilar envelopes, we controlled the valence of envelope for timbre identification and compensated for envelope reconstruction from fine structure information. Our results show that NH subjects utilize envelope and fine structure interchangeably, whereas CI subjects demonstrate overwhelming reliance on temporal envelope. When chimeras were created from dissimilar envelope instrument pairs, NH subjects utilized a combination of envelope (p = 0.008) and fine structure information (p = 0.009) to make timbre judgments. In contrast, CI users utilized envelope information almost exclusively to make timbre judgments (p < 0.001) and ignored fine structure information (p = 0.908). Interestingly, when the value of envelope as a cue was reduced, both NH subjects and CI users utilized fine structure information to make timbre judgments (p < 0.001), although the effect was quite weak in CI users. Our findings confirm that impairments in fine structure processing underlie poor perception of musical timbre in CI users.